2019
DOI: 10.29103/mjml.v2i1.2122
|View full text |Cite
|
Sign up to set email alerts
|

Students Self Regulated Learning in Numerical Methods Course using Computational Mathematics Teaching Materials

Abstract: Self regulated learning is a learning system applied in universities. Therefore, self regulated learning is needed by students in taking courses in college. Based on the results of previous studies found that students self regulated learning is still low. This study aims to improve students self regulated learning by using computational mathematics teaching materials in numerical method courses. The method used in this study is quasi-experimental with non-equivalent control group design. Result of this study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The results of the current study represented that the PMSMT could display flexibility, and form and use heuristic strategies based on the context and their geometric thinking. It was observed that they could produce problem solutions by flexibly and using and creating strategies effectively after the instructional sequence, Moreover, it can be stated that they could represent these behaviors and skills by developing their geometric thinking and creating problem solving strategies as encouraged in previous research (A'yun et al, 2021;Baist et al, 2019;Mulyatna et al, 2021). Also, it can be stated that the PMSMT became more successful geometry problem solvers by developing their flexibility.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results of the current study represented that the PMSMT could display flexibility, and form and use heuristic strategies based on the context and their geometric thinking. It was observed that they could produce problem solutions by flexibly and using and creating strategies effectively after the instructional sequence, Moreover, it can be stated that they could represent these behaviors and skills by developing their geometric thinking and creating problem solving strategies as encouraged in previous research (A'yun et al, 2021;Baist et al, 2019;Mulyatna et al, 2021). Also, it can be stated that the PMSMT became more successful geometry problem solvers by developing their flexibility.…”
Section: Discussionmentioning
confidence: 81%
“…In other words, in the present study, it was observed that the HLT supported by effective activities performed using GeoGebra encouraged problem solving since the PMSMT could improve their geometrical thinking skills and levels so that they could create new problem-solving strategies. There exist previous research whose findings encourage the development of problem solving skills (Sudarsono et al,, 2021) and geometrical thinking through instructional sequences (A'yunet al,2021;Baist et al, 2019;Hendroanto et al, 2019;Mulyatna et al, 2021;Rizki et al, 2018;Yudianto et al, 2018)With this motivation, it can be stated that the instructional sequence enacted based on the designed HLT could enhance the development of problem solving performance, and flexibility and strategy use. The reason behind this result might be affected by the tasks on GeoGebra.…”
Section: Discussionmentioning
confidence: 92%
“…Sin embargo, con el uso de las herramientas computacionales puede generar un reto aun mayor en el aprendizaje de los métodos numéricos ya que no solo requiere habilidades matemáticas si no un conocimiento en un lenguaje de programación. [12] II. METODOLOGÍA Considerando los principios de la metodología del aprendizaje basado en problemas, se estructuro una propuesta de enseñanza-aprendizaje para el curso de métodos numéricos teniendo objetivos pensados desde el estudiante y el docente.…”
Section: Fig 1 Etapas Del Aprendizaje Activounclassified
“…This is because mathematics is one of the subjects that need attention from research in the field of education. Other studies, for example (Baist et al, 2019;Mulyatna et al, 2021;A'yun et al, 2021) found that mathematics lessons not only foster critical thinking skills, but also provoke students' ability to be creative through solutions. mathematical problem.…”
Section: Introductionmentioning
confidence: 96%